Prefrontal cortical thinning links to negative symptoms in schizophrenia via the ENIGMA consortium. Issue 1 (26th May 2017) - Walton, E.; Hibar, D. P.; van Erp, T. G. M.; Potkin, S. G.; Roiz-Santiañez, R.; Crespo-Facorro, B.; Suarez-Pinilla, P.; van Haren, N. E. M.; de Zwarte, S. M. C.; Kahn, R. S.; Cahn, W.; Doan, N. T.; et al.
Abstract : Background: Our understanding of the complex relationship between schizophrenia symptomatology and etiological factors can be improved by studying brain-based correlates of schizophrenia. Research showed that impairments in value processing and executive functioning, which have been associated with prefrontal brain areas [particularly the medial orbitofrontal cortex (MOFC)], are linked to negative symptoms. Here we tested the hypothesis that MOFC thickness is associated with negative symptom severity. Methods: This study included 1985 individuals with schizophrenia from 17 research groups around the world contributing to the ENIGMA Schizophrenia Working Group. Cortical thickness values were obtained from T1-weighted structural brain scans using FreeSurfer. A meta-analysis across sites was conducted over effect sizes from a model predicting cortical thickness by negative symptom score (harmonized Scale for the Assessment of Negative Symptoms or Positive and Negative Syndrome Scale scores). Results: Meta-analytical results showed that left, but not right, MOFC thickness was significantly associated with negative symptom severity ( β std = −0.075; p = 0.019) after accounting for age, gender, and site. This effect remained significant ( p = 0.036) in a model including overall illness severity. Covarying for duration of illness, age of onset, antipsychotic medication or handedness weakened the association of negative symptoms with left MOFC thickness. As part of a secondary analysis including 10 other prefrontal regions further associations in the left lateral orbitofrontal gyrus and pars opercularis emerged. Conclusions: Using an unusually large cohort and a meta-analytical approach, our findings point towards a link between prefrontal thinning and negative symptom severity in schizophrenia. This finding provides further insight into the relationship between structural brain abnormalities and negative symptoms in schizophrenia.